Seismic responses of steel frame structures with self-centering energy dissipation braced on shape memory alloy cables. Issue 9 (July 2019) - Dong, Huihui; Du, Xiuli; Han, Qiang
Shape memory alloys have attracted a great deal of attention in civil engineering due to their excellent super elastic and moderate energy dissipating capabilities. At present, the shape memory alloy cables have been developed to meet the large size demand for practical applications. This article carries out numerical studies on the seismic responses of the steel frame with self-centering energy dissipation braced on shape memory alloy cables (SMA-SCEB) using OpenSees. The mechanical properties of the shape memory alloy cables were experimentally investigated first and compared to the traditional shape memory alloy wires/bars. Experimental results show the excellent super-elastic property of the shape memory alloy cables. A SMA-SCEB device is then proposed, and quasi-static cyclic loading tests are performed to evaluate its hysteretic behavior. The SMA-SCEB device is installed in the steel frame structure to enhance its seismic performances. Nonlinear dynamic analyses are carried out to examine its seismic responses. For comparison, the performance of self-centering energy dissipation brace with pre-tensioned basalt fiber–reinforced polymer cables (BFRP-SCEB) is also studied. Numerical results demonstrate that the self-centering energy dissipation brace can significantly reduce the residual drift ratio of the structure. In particular, the steel frame structure equipped with SMA-SCEBs suffers smaller peak acceleration than the one with the BFRP-SCEBs.